The Impact of Cancer on Mental Health - Ugur , Kübra (International Journal of Membrane Science and Technology, 2023)
Cancer cases have grown significantly more dangerous as people's life expectancies have increased. In addition, cancer patients may experience serious mental health issues that hinder their recovery. There is a gap in cancer treatment where patients are frequently only treated for their cancer and the effects of cancer on mental health are usually ignored. Several psychiatric care programs are available to patients, but few people are aware of them, and cancer patients are not questioned regarding their attraction to these programs. The aim of the study is to analyze the impact of cancer on anxiety and depression level of cancer patients and to understand which prevention program is found more interesting by cancer patients. Seventy patients participated in this study. Hospital Anxiety and Depression Scale (HADS) has been used to measure anxiety and depression. According to the results, the average anxiety level was 9.36 ± 4.33, and the average depression level was 10.49 ± 3.50. Based on the program selection, the majority of participants selected "Support Groups" with a rate of 41.40%, and "Educational Programs" with a rate of 31.40%. In conclusion, the average anxiety level was at the borderline, and the average depression level was abnormal. This study shows that the mental health of cancer patients is neglected, and this issue is not sufficiently addressed. Future studies may focus on how to solve this problem more effectively and how to raise more awareness about the mental health of cancer patients.